Have They Already Emerged? Mapping the Population of National Interest Organisations in Post-Communist Poland. Issue 5 (28th May 2022) - Rozbicka, Patrycja; Kamiński, Paweł
Abstract: While political parties provide a key channel for political representation, organised interests can also be an important mechanism. A valid question is whether a system of interest groups is capable of ensuring the representation of a variety of public and private interests. Addressing this conundrum requires data that map the essential traits of organised interest groups in a given country, including their number (density) and types (diversity). This article explores the density and composition of the Polish system of organised interests. The previously unexplored system-level approach delivers insights into the nature of the system and also provides a framework for the subsequent conceptualisation of advocacy and lobbying dynamics.